Konsep Dakwah Dalam Memelihara Dan Pemberdayaan Masyarakat Di Sekitar Hutan (Studi Kasus Di Kabupaten Kerinci) - Ivan Sunata (Jurnal Dakwah dan Komunikasi, 2017)
Propagation as a pillar of Islam in conveying God's revelation must be interpreted broadly, not just propaganda materials related subject matter (tawhid) but also about the preservation of nature and the welfare of the people (society). Forests should be managed jointly between the public and the government that maintained continuity, while people living in the vicinity to prosperous. This research is field research field with qualitative research type, research method used is action research or action study with participatory approach, this approach emphasizes the importance of dialogue process in research. In this case can be seen how the concept of da'wah in the maintenance and empowerment of communities around the forest in Kerinci district